The predictive value of TNF family for pulmonary tuberculosis: a pooled causal effect analysis of multiple datasets - Mo, Wenxiu; Cui, Zhezhe; Zhao, Jingming; Xian, Xiaomin; Huang, Minying; Liu, Jun (Frontiers in Immunology, 2024)
Objective Despite extensive research on the relationship between pulmonary tuberculosis (PTB) and inflammatory factors, more robust causal evidence has yet to emerge. Therefore, this study aim to screen for inflammatory proteins that may contribute to the susceptibility to PTB in different populations and to explain the Tumor necrosis factor family would be Predicted Active pulmonary tuberculosis: A Pooled Causal Effect Analysis of Multiple Datasets 删除[Mˉwˉx]: Although numerous studies have been conducted on pulmonary tuberculosis (PTB) and inflammatory factors 删除[Mˉwˉx]: a 删除[Mˉwˉx]: the aim of 删除[Mˉwˉx]: